1994
DOI: 10.1080/00071669408417675
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different dietary supplemental fats and oils on the tissue fatty acid composition and growth of female broilers

Abstract: 1. A study was undertaken to examine the effect of supplementation of diets with fats of different chain length and degree of unsaturation on the performance, carcase characteristics and tissue fatty acid composition of broilers. 2. Three hundred and sixty 19-day-old female broilers were fed on diets containing supplemental fat/oil (50 g/kg) in the form of beef tallow (BT) (diet T-T), soyabean oil (SBO) (diet S-S), rapeseed oil (RSO) (diet R-R), marine oil (MO) (diet M-M) or binary mixtures (0.5:0.5 w/w) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
65
1
10

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 17 publications
13
65
1
10
Order By: Relevance
“…Scaife et al (1994) fed female broilers with rations containing different sources of lipids (beef tallow, soybean oil, canola oil, marine fish oil or a mixture of these oils) and observed that live weight was significantly higher when soybean oil was used. Birds fed with canola oil also showed higher intake and higher weight.…”
Section: Degummed Soybean Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaife et al (1994) fed female broilers with rations containing different sources of lipids (beef tallow, soybean oil, canola oil, marine fish oil or a mixture of these oils) and observed that live weight was significantly higher when soybean oil was used. Birds fed with canola oil also showed higher intake and higher weight.…”
Section: Degummed Soybean Oilmentioning
confidence: 99%
“…Therefore, it has been suggested the inclusion of low dietary levels of fish oil together with another source of linoleic fatty acid to obtain an acceptable product with increased ratio between ω-3:ω-6 fatty acids. Scaife et al (1994) have utilized beef tallow, soybean oil, colza oil, oil of marine fish or mixtures of these oils in female broiler diets. The relation ω-6:ω-3 was significantly increased with the inclusion of soybean oil and decreased with the inclusion of marine fish oil.…”
Section: Fish Oilmentioning
confidence: 99%
“…The existing potential for the modification of dietary fatty acids has proved to be a viable method of value adding to poultry products since dietary fatty acids are absorbed and deposited in the body tissue without significant modification by birds (González-Esquerra & Leeson, 2001). Scaife et al (1994) and Lopez-Ferrer et al (1999) reported that the lipid composition of broiler meat is modified according to the fatty acid profile of the dietary lipids sources within a week of feeding the diets.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary administration of long-chain n-3 polyunsaturated fatty acids (PUFA) may increase their content in the lipid fraction of animal products (Scaife et al, 1994) and could be a positive fatty-acid modulator in human diets (Lewis et al, 2000). The fat from cold marine fish contains high concentrations of docosapentaenoic (DPA) and docosahexaenoic (DHA) acids and can efficiently increase n-3 fatty acid content in poultry diets (Miller and Robisch, 1969).…”
Section: Introductionmentioning
confidence: 99%